PENDAPATAN USAHATANI CABAI MERAH DI KECAMATAN KALIANDA KABUPATEN LAMPUNG SELATAN - Ulpah Choirun Nisa; Dwi Haryono; Ktut Murniati (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This research aims to analyze the income of red chili farming in Kalianda Sub-District of South Lampung Regency.  This research is conducted by using census method, involving 30 farmer respondents.  Data were collected in October – November 2016.  The objective is analyzed descriptively and quantitatively using R/C ratio.  The results showed that the income of red chili farming is Rp91,519,527.08/ha and the value of R/C on total cost is 2.95.Key words: farming, income, red chili